Public Value of Social Piety of Wayang Wali Culture as a Trigger for Cultural Community Capacity Building Policy in Blitar - Romadhoni, Moh Suma Firman; Yusuf, Bima Sakti Putra; Sari, Adma Novita; Widyangga, Pressylia Aluisina Putri; Mardianto, M. Fariz Fadillah (Department of Public Administration, 2024)
This study aims to explore the public value contained in the social piety dimension of Wayang Wali culture, as a driving instrument for policy development of the capacity of cultural communities and the people of Blitar. The data collection method used in this research is a qualitative study with unstructured observation and documentation study. The data were analysed using componential techniques to find the interrelationship of values contained within the scope of the research object. We found that there are elements of social piety in Wayang Wali culture as a public value in the community, and can be used as a driving value for cultural and community capacity development. The government or relevant authorities can make Wayang Wali culture an instrument of social development and capacity building of cultural communities and society as a local identity.